Kajian Brand Strategy Roadmap (Studi Kasus Starbucks Coffee) - Sultan Arif Rahmadianto (Citradirga : Jurnal Desain Komunikasi Visual dan Intermedia, 2019)
Today, business competition is no longer refers to the problem of product quality but on the issue of brand. A good brand will increase the quality of the product in the eyes of consumers by itself. The purpose of this research is to find out and analyze the brand strategy in brand "Starbucks" by using the approach brand roadmap. From the analysis that has been done based on contextual internal (core values) and externally (the core of the message, personality, and icon). Starbucks's Coffee brand illustrates that Starbucks as a brand that is very consistent in giving an overview on the public so that the consequent Starbucks and professional brand. The benefits of this research is to provide an overview of how to convey knowledge brand so easily communicated and understood by any person either, employees, associates, customers or investors who interact with the brand.